Molecular characterization and classification of a clip domain containing peptidase from the ectoparasite Lepeophtheirus salmonis (Copepoda, Crustacea). - Skern-Mauritzen, R., P. Frost, L.A. Hamre, H. Kongshaug & F. Nilsen (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2007)
Clip domain containing serine peptidases (CSPs) include one or more N-terminal clip domain(s) and a C-terminal serine peptidase domain that shares traits with both chymotrypsin and trypsin. CSPs are found in arthropods and are involved in embryonic patterning, immune responses and blood clotting. Among crustaceans only one CSP, which activates prophenoloxidase in crayfish, have previously been reported. We here present LsCSP1, the first CSP found in copepods. LsCSP1 is expressed in the subcuticular tissue and the transcription appears to be upregulated during development. In conjunction with previous studies of CSPs, this study suggests that LsCSP1 may play a role in the immune responses of L. salmonis. Phylogenetic and structural analyses indicate that the CSPs and catalytically inactive CSP homologs (CSPHs) constitute a monophyletic lineage.